Analyze of Customer Satisfaction BSI Mobile PT. Bank Syariah Indonesia Tbk. - Verawaty Verawaty (Research Synergy Foundation, 2022)
The development of science and technological advances in Islamic banking has resulted in changes in the way of consucting transactions in society. Information technology based transaction service media of PT. BSI Mobile opens opportunities to offer added value for Bank Syariah Indonesia Tbk. This research purpose was to analyze customer satisfaction levels with the users of BSI Mobile at PT. Bank Syariah Indonesia Tbk. Research uses a quantitative descriptive with a population of BSI Mobile users at PT. Bank Syariah Indonesia Tbk in Makassar. Data analysis techniques using validity, reliability and Cartesian Diagrams. A sample of 100 respondents, where data collection was done by questionnaire. The level of satisfaction based on satisfaction based and expectation of BSI Mobile customers. The result that respondent were very satisfied with BSI Mobile’s service, while from the quantitative analysis, the level of customer interest/ expectations was quite high, with an average of 4,35 and the performance received was satisfactory of 4,26 with a comformity level of 97,80%. Limitations research uses service quality which consist of dimensions of tangible, reliability, responsiveness, assurance, emphaty and doesn’t add other dimensions.